2022
DOI: 10.3389/fimmu.2022.997851
|View full text |Cite
|
Sign up to set email alerts
|

A network view of human immune system and virus-human interaction

Abstract: The immune system is highly networked and complex, which is continuously changing as encountering old and new pathogens. However, reductionism-based researches do not give a systematic understanding of the molecular mechanism of the immune response and viral pathogenesis. Here, we present HUMPPI-2022, a high-quality human protein-protein interaction (PPI) network, containing > 11,000 protein-coding genes with > 78,000 interactions. The network topology and functional characteristics analyses of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Indeed, hubs and bottlenecks are key targets for various pathogens, including viruses, bacteria, and eukaryotic pathogens, across plant and animal interactomes. For instance, following the construction of a comprehensive human interactome, analysis of network centrality unveiled that pan-viral targets predominantly consist of hubs positioned at the network's core and enriched in fundamental biological processes [19]. A meta-analysis of host-virus interactions across 17 different viruses indicated that viruses tend to target bottlenecks and hubs.…”
mentioning
confidence: 99%
“…Indeed, hubs and bottlenecks are key targets for various pathogens, including viruses, bacteria, and eukaryotic pathogens, across plant and animal interactomes. For instance, following the construction of a comprehensive human interactome, analysis of network centrality unveiled that pan-viral targets predominantly consist of hubs positioned at the network's core and enriched in fundamental biological processes [19]. A meta-analysis of host-virus interactions across 17 different viruses indicated that viruses tend to target bottlenecks and hubs.…”
mentioning
confidence: 99%